Feeding jejunostomy following esophagectomy may increase the occurrence of postoperative small bowel obstruction. Issue 37 (16th September 2022) - Nakai, Tomoki; Kitadani, Junya; Ojima, Toshiyasu; Hayata, Keiji; Katsuda, Masahiro; Goda, Taro; Takeuchi, Akihiro; Tominaga, Shinta; Fukuda, Naoki; Nagano, Shotaro; Yamaue, Hiroki
Abstract : This study aimed to clarify the characteristics and treatment of bowel obstruction associated with feeding jejunostomy in patients who underwent esophagectomy for esophageal cancer. In this single-center retrospective study, 363 patients underwent esophagectomy with mediastinal lymph node dissection for esophageal cancer at the Wakayama Medical University Hospital between January 2014 and June 2021. All patients who underwent esophagectomy routinely underwent feeding jejunostomy or gastrostomy. Feeding jejunostomy was used in the cases of gastric tube reconstruction through the posterior mediastinal route or colon reconstruction, while feeding gastrostomy was used in cases of retrosternal route gastric tube reconstruction. Nasogastric feeding tubes and round ligament technique were not used. Postoperative small bowel obstruction occurred in 19 of 197 cases of posterior mediastinal route reconstruction (9.6%), but in no cases of retrosternal route reconstruction because of the feeding gastrostomy ( P  < .0001). Of the 19 patients who had bowel obstruction after feeding jejunostomy, 10 patients underwent reoperation (53%) and the remaining 9 patients had conservative treatment (47%). The cumulative incidence of bowel obstruction after feeding jejunostomy was 6.7% at 1 year and 8.7% at 2 years. Feeding jejunostomy following esophagectomy is a risk factor for small bowel obstruction. We recommend feeding gastrostomy inserted from the antrum to the jejunum in the cases of gastric tube reconstruction through the retrosternal route or nasogastric feeding tube in the cases of reconstruction through the posterior mediastinal route.